KESALAHAN MAHASISWA CALON GURU SD DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA - Fitri Apriani (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2018)
This research was qualitative descriptive research that aimed to describe errors made by university students in solving Mathematic problems. The subject of this research were seventh semester students of Primary School Education Study Program of STKIP Muhammadiyah Bangka Belitung that were taking Mathematic Problem Solving subject with the sample of one class students taken randomly. There were 45 students in one class. Data collected through a written test, documentation, and interviews. The tests usedin this research was essay written test. Data were analyzed with the reduction of data, coding data, and conclusions. Based on the result of the research, it was found that there were 13 students made error in understanding the problem, 17 students made error in planning the problem solving, 4 students made error in implementing the plan, and 8 students made error in revising the process and the result.